Performing postmortem examinations on small animals in first‐opinion practice. Issue 2 (4th March 2022) - Lee, Alison; Wasques, Danilo Gouveia
Abstract : Background : Postmortem examination (PME) is often viewed as a specialised procedure, but it is listed as a Day One Competence by the RCVS. The ability to perform a PME confidently in first‐opinion practice may allow veterinarians to confirm their clinical diagnoses, and provides an opportunity for self education and quality control. It is also an important tool for disease surveillance. Clear communication with the animal's owner and obtaining consent are essential before a PME is undertaken. Veterinarians should be aware of situations in which performing a PME may not be appropriate in first‐opinion practice (eg, legal/forensic cases). Aim of the article : This article discusses the considerations that must be made before undertaking a PME in small animals and outlines the steps involved in the procedure.